The Relationship of Mother’s Perception With Breast Milk Exclusive at Pomalaa Health Center - Muliani Muliani; Cholik Harun Rosjidi; Ellyani Abadi; Muhammad Uksim (KLASICS, 2023)
The number of exclusive breastfeeding globally, although there has been an increase, this number has not increased significantly. One of the factors that influence exclusive breastfeeding is the value or attitude of the mother. The purpose of this study was to determine the relationship between mother's perception and exclusive breastfeeding at the Pomalaa Health Center. This research was carried out at the Pomalaa Health Center in June 2022 involving a sample of 51 respondents. The sampling technique used is the Saturated Sampling technique. Data collection used a research instrument in the form of a questionnaire. Data were analyzed using the chi-square test with the help of a computer. The results showed that 21 people (41.2%) gave exclusive breastfeeding and 30 people (58.8%) did not and 25 people (49%) had good perceptions and 26 people (51 %) who had poor perceptions and there was a relationship between mothers' perceptions of exclusive breastfeeding in the working area of the Pomalaa Health Center based on a Ï value of 0.001 (<0.05). It is recommended that mothers add insight regarding the benefits of exclusive breastfeeding for both children and mothers